Integrated QR Code-Based Cafe Ordering with Point of Sale and Electronic Receipt - Hasna Anggun Nafisa; Erna Hudianti Pujiarini (Journal of Information Systems and Technology Research, 2026)
The rapid growth of information technology has driven digital transformation in various business sectors, including the culinary industry. One innovation that is widely adopted is the use of a QR Code-based ordering system to increase service efficiency and transaction transparency. This research aims to design and visualize a QR Code-based cafe ordering system that is integrated with a Point of Sale (POS) system and electronic receipt features. System development follows the Waterfall methodology, which consists of the stages of requirements analysis, system design, implementation, and functional testing. The result of this research is a web-based prototype that represents the digital ordering process, starting from scanning the QR Code, selecting the menu, sending the order, confirming payment by the cashier, and accessing digital receipts. Functional testing shows that all key system features operate according to specified requirements. Even though the system is still a prototype and has not been integrated with a database or back-end system, this system is able to describe system workflow and user interactions effectively. The proposed prototype can be an academic reference and foundation for the development of a QR Code-based cafe ordering system in the future.